Contract farming for improving farmers’ incomes: from Resource-Based View - Que Yang; Que Yang; Xin Zhang; Hua Peng; Dongsheng Sun (Frontiers in Sustainable Food Systems)
IntroductionThe sales revenue of agricultural products is pivotal for augmenting farmer income and fostering sustainable agricultural economic development.MethodsThis study employs propensity score matching (PSM) and establishes a structural analytical framework grounded in the Resource-Based View (RBV) to mitigate endogeneity concerns. Fuzzy-set qualitative comparative analysis (fsQCA) is applied to examine survey data from 111 vegetable distribution firms, exploring pathways for enhancing sales revenue under two distinct acquisition models.ResultsThe findings reveal that: (1) fsQCA empirical analyses demonstrate that physical, human, and organizational capital collectively contribute to revenue enhancement. (2) Under the contract farming model, both physical and human capital emerge as core drivers of sales revenue, whereas non-contract farming configurations are predominantly characterized by human capital as the central determinant. (3) While both models emphasize human capital, the contract farming framework further underscores the integral role of physical capital across the entire value chain.DiscussionThis study integrates the Resource-Based View (RBV) with fuzzy-set Qualitative Comparative Analysis (fsQCA) to uncover the synergistic effects of three types of capital (physical, human, and organizational) on vegetable sales revenue, thereby overcoming the limitations of traditional research that focuses narrowly on single production factors. Furthermore, it constructs a multi-dimensional theoretical framework and proposes differentiated resource-driven mechanisms, which helps policy makers to optimize various conditions in a targeted manner and promote the improvement of farm products sales revenue.